Pencegahan stunting melalui edukasi gizi seimbang dan pemanfaatan pekarangan untuk kebun gizi dan toga di Desa Bayu, Kecamatan Darul Imarah, Aceh Besar - Rasidah, Rasidah; Nuraskin, Cut Aja; Al Rahmad, Agus Hendra; Reca, Reca; Salfiyadi, Teuku; Mardiah, Ainun; Usrina, Nora (Jurnal PADE: Pengabdian & Edukasi, 2025)
Stunting is a chronic nutritional problem that affects child growth and has long-term impacts on quality of life. This community service activity aimed to reduce stunting rates and empower communities in addressing family nutritional deficiencies. The methods used included counseling, training, and community group mentoring. The results showed an increase in mothers’ understanding of stunting by 42%, an improvement in the number of families applying balanced nutrition from 56% (pre-test) to 86% (post-test), as well as the establishment of 52% new nutrition and medicinal plant gardens (TOGA) with active participation from 84% of participants. This activity demonstrates that educational and participatory community-based approaches are effective in raising awareness and fostering community independence in stunting prevention.